Dampak Fasilitas Hak Paten dan Halal dari pemerintah Terhadap Peningkatan UMKM di Surabaya - ALMUBAROK, HUSNI DWI DHUHAWAN; kusmayati, nindya kartika; Muslikhun; Kurniawan, Taufik (Universitas Kadiri, 2023)
Many UMKM entrepreneurs have recently plagiarized products sold freely on the market, resulting in losses for the first entrepreneurs who become victims of product plagiarism. Patents are exclusive rights used to protect innovative plagiarism behavior in products being developed. The reviewer wanted to examine whether there was any influence on patents & halal certification by increasing UMKM. This experiment was conducted with a sample of 32 respondents. This study uses a quantitative design with several questions in the questionnaire. The results of this study were declared valid and reliable, normally distributed, free of heteroscedasticity, and free of multicollinearity. A simple linear regression model was obtained by testing 1 (one) independent variable on the dependent variable Y = 17.347 + 0.557 X1 + e, which means that the independent variable is Patent & Halal (X1) simultaneously has a positive and significant effect on increasing UMKM (Y). Therefore, entrepreneurs must refer to consumer trust because patents and halal certification are interdependent and make the market attractive to consumers